Toruński Informator "Solidarności" . pismo RKW "Solidarność" Regionu Toruńskiego, no. 129, 1985 - Cichoń, Wiesław; Spandowski, Roman; Kaczor, Andrzej; Sienkiewicz, Radek; Borek, Piotr; Musielak, Ryszard (s.n.], 1985)
Creation and circulation: From issue no. 10=227(1989)published legally